Apoptosis induction by extracorporeal photopheresis is enhanced by increasing the 8‐methoxypsoralen concentration and by replacing plasma with saline. Issue 10 (24th August 2021) - Hähnel, Viola; Brosig, Andreas‐Michael; Ehrenschwender, Martin; Burkhardt, Ralph; Offner, Robert; Ahrens, Norbert
Abstract: Background: Extracorporeal photopheresis (ECP), an apheresis‐based therapy for various immunological diseases, works mainly by inducing apoptosis in lymphocytes. Several factors influence the efficacy of ECP with the photosensitizer 8‐methoxypsoralen (8‐MOP) and ultraviolet light A (UVA). This study aimed to optimize treatment by varying the 8‐MOP starting concentration and the cell suspension medium. Materials and Methods: All patients ( n = 13) included in this study received photopheresis as medically indicated. Cells collected with a Spectra Optia apheresis system were suspended in plasma or physiological saline (NaCl) and incubated with 200 ng/ml versus 340 ng/ml photosensitizer before UVA irradiation (Macogenic G2 or UVA PIT system). Lymphocyte apoptosis and caspase activity were analyzed by flow cytometry and fluorimetry, and residual 8‐methoxypsoralen concentrations by liquid chromatography–mass spectrometry. Results: Raising the 8‐MOP starting concentration significantly increased lymphocyte apoptosis, with values of 22% versus 35% (plasma) and 28%–46% (NaCl) at 24 h post‐ECP and 37% versus 86% (plasma) and 74% versus 97% (NaCl) at 48 h for 200 ng/ml versus 340 ng/ml. Pre‐transfusion residual 8‐MOP levels were 168 ng/ml (plasma) and 162 ng/ml (NaCl) versus 290 ng/ml (plasma) and 266 ng/ml (NaCl) for the lower versus higher dose, respectively. Discussion: Hence, 8‐MOP concentration influences the efficacy of photopheresis as lymphocyte apoptosis rates were significantly higher with the higher starting concentration and with NaCl versus plasma. This indicates that increased 8‐MOP starting doses and saline as additional suspension medium could help in improving ECP's efficacy.